Solid electrolyte contact surface adjustment material and its hybrid electrolyte system

By using solid electrolyte contact surface adjustment materials in inorganic solid electrolytes, the problem of high interface impedance is solved and better electrochemical performance is achieved.

CN112701346BActive Publication Date: 2025-03-11PROLOGIUM TECHNOLOGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202011096063.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-22
Filing Date
2020-10-14
Publication Date
2025-03-11
Estimated Expiration
2040-10-14

AI Technical Summary

Technical Problem

Inorganic solid electrolytes have high interfacial impedance problems in secondary chemical energy applications, resulting in poor electrochemical performance.

Method used

A solid electrolyte contact surface adjustment material is used, which is mixed with a polymer substrate that can move metal ions and an additive material capable of dissociating metal salts to form a bridge to reduce interface impedance.

Benefits of technology

Through surface-to-surface or approximately wettability contact mode, the interface impedance of the solid electrolyte is reduced and the electrochemical performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112701346B_ABST
    Figure CN112701346B_ABST
Patent Text Reader

Abstract

The present invention provides a solid electrolyte contact surface adjustment material and a mixed electrolyte system thereof. The solid electrolyte contact surface adjustment material is mainly composed of a polymer matrix that allows metal ions to move inside the material and an additive material that can dissociate metal salts and act as a plasticizer. The solid electrolyte contact surface adjustment material is applied to a solid electrolyte surface, and a face-to-face conduction method is constructed by the material properties of the solid electrolyte contact surface adjustment material to solve the high interface impedance problem when the solid electrolyte contacts another particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrolyte in an electrochemical system, in particular to a solid electrolyte contact surface adjusting material and a mixed electrolyte system containing the solid electrolyte contact surface adjusting material. Background Art

[0002] In today's era of energy crisis and energy revolution, secondary chemical energy plays a very important role, especially metal ion batteries with advantages such as high specific energy and specific power, such as sodium ion batteries, aluminum ion batteries, magnesium ion batteries, or lithium ion batteries. The application scope of these batteries ranges from information and consumer electronics products, and has recently expanded to energy and transportation categories.

[0003] The common electrolyte systems in secondary chemical energy can be mainly divided into liquid electrolyte systems and solid electrolyte systems. The above-mentioned solid electrolyte systems also cover inorganic electrolytes and organic polymer electrolytes. In order to adapt to battery systems with working voltages as high as 3-4V, such as lithium-ion batteries, the liquid electrolyte system excludes the use of water as a solvent, but instead adopts organic solvents and electrolyte salts that are not easily decomposed under high voltage as the main components. However, these organic solvents are flammable, volatile, and cause battery leakage and cause explosions and fires. Based on safety considerations, the electrolyte system has shifted from a liquid to a solid electrolyte system with higher safety, especially a highly thermally stable inorganic solid electrolyte system, such as an oxide solid electrolyte. However, the non-deformable nature of oxide solid electrolytes causes some application problems. For example, the oxide solid electrolytes are mainly point-to-point contacts with each other or between the oxide solid electrolyte and the active material of the polar layer at the interface, and cannot be contacted with another material through a surface-to-surface method or a coating pattern that is close to wettability, such as a liquid electrolyte or a colloidal electrolyte. Therefore, high interface impedance has become one of the important bottlenecks of oxide solid electrolytes in the application of secondary chemical energy.

[0004] In view of this, the present invention proposes a novel solid electrolyte contact surface adjustment material and a hybrid electrolyte system thereof to solve the above-mentioned problems. Summary of the invention

[0005] The main purpose of the present invention is to provide a solid electrolyte contact surface adjustment material and a mixed electrolyte system thereof to solve the high interface impedance problem of inorganic solid electrolytes.

[0006] The present invention provides a solid electrolyte contact surface adjusting material for metal electrochemical system. The solid electrolyte contact surface adjusting material is mixed with a polymer matrix that allows metal ions to move inside the material and an additive material that can dissociate metal salts and serve as a plasticizer.

[0007] The present invention also proposes a hybrid electrolyte system containing the above-mentioned solid electrolyte contact surface adjustment material, which includes a first particle, which is a first inorganic solid electrolyte; a second particle, which is selected from a second inorganic solid electrolyte, a passive ceramic material or an active material; and a bridging portion, which is located between the first particle and the second particle, and the bridging portion is formed by the above-mentioned solid electrolyte contact surface adjustment material, and the solid electrolyte contact surface adjustment material connects the first particle and the second particle to form an ion transfer pathway.

[0008] The present invention also proposes a hybrid electrolyte system containing the above-mentioned solid electrolyte contact surface adjustment material, which includes a first particle, which is a first inorganic solid electrolyte; a second particle, which is selected from a second inorganic solid electrolyte, a passive ceramic material or an active material; and a first shell layer, which covers the outer surface of the first particle; wherein the first shell layer is formed by the above-mentioned solid electrolyte contact surface adjustment material, and the solid electrolyte contact surface adjustment material connects the first particle and the second particle to form an ion transfer pathway.

[0009] The following detailed description is made through specific embodiments to make it easier to understand the purpose, technical content, characteristics and effects achieved by the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1a It is a schematic diagram of a hybrid electrolyte system constructed using the solid electrolyte contact surface adjustment material of the present invention.

[0011] Figure 1b It is a schematic diagram of the contact surface between the bridging portion of the present invention and the inorganic solid electrolyte.

[0012] Figure 1c-1g They are schematic diagrams of different embodiments of the hybrid electrolyte system of the present invention.

[0013] Figure 2a-2h They are schematic diagrams of different embodiments of the hybrid electrolyte system of the present invention.

[0014] Figure 2a' yes Figure 2a A partial enlarged view of .

[0015] Figure 3a-3f They are schematic diagrams of different embodiments of the hybrid electrolyte system of the present invention.

[0016] Figure 4 This is a schematic diagram of the relationship between ionic conductivity and frequency of different materials. DETAILED DESCRIPTION

[0017] In order to make the advantages, spirit and features of the present invention more easily and clearly understood, the following will be described and discussed in detail with reference to the drawings and embodiments. It should be noted that these embodiments are only representative embodiments of the present invention, and the embodiments and claims of the present invention are not limited to these embodiments. The purpose of providing these embodiments is only to make the disclosure of the present invention more thorough and easy to understand.

[0018] The terms used in the various embodiments disclosed in the present invention are only used for the purpose of describing specific embodiments, and are not intended to limit the various embodiments disclosed in the present invention. Unless otherwise clearly indicated, the singular form used also includes the plural form. Unless otherwise specified, all terms (including technical terms and scientific terms) used in this specification have the same meanings as those commonly understood by ordinary technicians in the field to which the various embodiments disclosed in the present invention belong. The above terms (such as those defined in a generally used dictionary) will be interpreted as having the same meaning as the contextual meaning in the same technical field, and will not be interpreted as having an idealized meaning or an overly formal meaning, unless clearly defined in the various embodiments disclosed in the present invention.

[0019] In the description of this specification, reference to the terms "embodiment", "specific embodiment", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments in a suitable manner.

[0020] In the description of the present invention, unless otherwise specified or limited, it should be noted that the terms "coupling", "connection" and "setting" should be understood in a broad sense. For example, it can be a mechanical connection or an electrical connection, or it can be the internal connection of two components, it can be a direct connection, or it can be connected through an intermediate medium. For those with general knowledge in this field, the specific meanings of the above terms can be understood according to the specific circumstances.

[0021] First, the solid electrolyte contact surface adjustment material of the present invention mainly comprises a polymer matrix that allows metal ions (such as lithium ions) to move inside the material and an additive material that can dissociate metal salts (such as lithium salts) and act as a plasticizer. In addition, the solid electrolyte contact surface adjustment material is also mixed with an ion supply material and a crystallization inhibition material. In the following description, the metal ions are described as lithium ions, and the metal salts are described as lithium salts.

[0022] The polymer matrix that allows lithium ions to move inside the material is a material that does not contain lithium ions itself (in the raw material state or in the initial stage of the electrochemical reaction) but can transfer lithium ions. For example, it can be selected from linear structural materials that do not contain salts, such as polyethylene oxide (PEO). Or it can be a material that can increase the mechanical strength of the film due to its cross-linking structure in addition to allowing lithium ions to move and transfer, such as polyethylene glycol diacrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), polyethylene glycol methyl ether (PEGME), polyethylene glycol dimethylether (PEGDME), polyethylene oxide / 2, (2-methoxyethoxy)-ethyl glycidyl ether copolymer (poly [ethylene oxide-co-2- (2-methoxyethoxy) ethylglycidyl ether] (PEO / MEEGE)). Or it can be a series of hyperbranched polymers, such as poly(bis(triethylene glycol)benzoate); a series of polynitriles, such as polyacrylonitrile (PAN), poly(methacrylonitrile) (PMAN), and poly(N-2-cyanoethyl)ethyleneamine (PCEEI).

[0023] The crystallization inhibiting material may be selected from materials having a better effect of reducing crystallinity, such as poly(ethyl methacrylate)(PEMA)), poly(methyl methacrylate)(PMMA)), poly(oxyethylene)), poly(cyanoacrylate)(PCA)), polyethylene glycol (PEG), poly(vinyl alcohol)(PVA), polyvinyl butyral (PVB), poly(vinyl chloride)(PVC), polyvinyl chloride-polyethyl methacrylate (PVC-PEMA), polyoxyethylene-polymethyl methacrylate (PEO-PMMA), poly(acrylonitrile-co-methyl methacrylate) copolymer (Poly(acrylonitrile-co-methyl methacrylate) copolymer, poly(vinyl chloride) (PVC), polyvinyl chloride-polyethyl methacrylate (PVC-PEMA), polyoxyethylene-polymethyl methacrylate (PEO-PMMA), poly ...PVA), polyvinyl butyral (PVB), polyvinyl chloride (PVC), polyvinyl chloride-polyethyl methacrylate (PVC-PEMA), polyoxyethylene-polymethyl methacrylate ( Poly(ethylene oxide)-co-ethylene carbonate (PEOEC), polyhedral oligomericsilsesquioxane (POSS), polyethylene carbonate (PEC), polypropylene carbonate (PPC), poly(ethyl glycidylether carbonate) (P(Et-GEC), poly(t-butyl glycidylether carbonate) (P(tBu-GEC)); cyclic carbonates series, such as poly(trimethylene carbonate) (PTMC);Polysiloxane-based series, such as polydimethylsiloxane (PDMS), polydimethylsiloxane-co-ethylene oxide (P(DMS-co-EO)), poly(siloxane-g-ethyleneoxide); Polyesters series, such as ethylene adipate, ethylene succinate, ethylene malonate; and, such as poly(vinylidenedifluoridehexafluoropropylene)(PvdF-HFP), poly(vinylidenedifluoride)(PvdF), poly(ε-caprolactone)(PCL). ;

[0024] The above-mentioned additive material capable of dissociating lithium salt and acting as a plasticizer can be selected from the series of plastic crystal electrolytes (PCEs), such as Succinonitrile (SN) [ETPTA / / SN; PEO / SN; PAN / PVA-CN / SN], N-ethyl-N-methylpyrrolidinium + N, N-diethylpyrrolidine (N-ethyl-N-methylpyrrolidinium, [C2mpyr] + Anions N, N-diethyl-pyrrolidinium, [C2epyr]), Quaternary alkylammonium (Quaternary alkylammonium), n-alkyltrimethylphosphonium ([P1,1,1,n]), decamethylferrocene (Decamethylferro-cenium, [Fe(C5Me5)2]), 1-(N,N-dimethylammonium)-2-(ammonium)ethane triflate ([DMEDAH2][Tf]2)), Anions = [FSI], [FSA], [CFSA], [BETA], LiSi(CH3)3(SO4), Trimethy(lithium trimethylsilylsulfate). Or it can be an ionic liquid, which can be selected from the imidazole series, such as bis(trifluoromethanesulfonyl)imide (ANION / Bis(trifluoromethanesulfonyl)imide), bis(fluorosulfonyl)imide (ANION / Bis(fluorosulfonyl)imide), trifluoromethanesulfonate (ANION / Trifluoromethanesulfonate). Or it can be an ammonium series, such as bis(trifluoromethanesulfonyl)imide (ANION / Bis(trifluoromethanesulfonyl)imide). Or it can be a pyridine series, bis(trifluoromethanesulfonyl)imide (ANION / Bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide (ANION / Bis(fluorosulfonyl)imide).Or the piperidine (PIPERIDINIUM) series, such as bis (trifluoromethanesulfonyl) imide (ANION / Bis (trifluoromethanesulfonyl) imide), bis (fluorosulfonyl) imide (ANION / Bis (fluorosulfonyl) imide).

[0025] The ion supply material may be a lithium salt, such as lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4) or lithium hexafluorophosphate (LiPF6).

[0026] Furthermore, the solid electrolyte contact surface adjustment material can also be mixed with a second dopant, which can be a nano-scale passive ceramic material (non-electrolyte oxide) or an inorganic solid electrolyte, or a conductive material. When the second dopant is a passive ceramic material, the amount of polymer substrate and additive materials used can be reduced, and the film-forming property can be improved. As a film-forming reinforcement material, silicon dioxide is used as an example of the material, and if it is a nano-scale inorganic solid electrolyte, in addition to reducing the amount of polymer substrate and additive materials used, it can also provide a high-speed ion conduction path. This inorganic solid electrolyte can be, for example, an oxide solid electrolyte or a sulfide solid electrolyte or other inorganic solid electrolyte. For example, when ions are transmitted in this solid electrolyte interface adjustment material, they can simply select the adjustment material to move, or they can also select the nano-scale inorganic solid electrolyte as the action path when touching the nano-scale inorganic solid electrolyte. If this second dopant is a conductive material, it will improve the conductivity, especially when used in the polar layer.

[0027] In addition, the present invention uses additive materials to improve the fluidity of the polymer substrate, so that the polymer substrate has higher room temperature ion conductivity and poor mechanical properties, and can be filled between solid electrolyte particles, or between solid electrolyte particles and another particle of different properties, to achieve surface-to-surface (non-point-to-point) or nearly wettable contact, thereby reducing the interface resistance of the solid electrolyte. In addition, because the additive materials, such as ionic liquids, do not volatilize, there will be no problem of flammable gas. At the same time, during the dehydration and drying process, the solid electrolyte contact surface adjustment material will not shrink in size and reduce ion conduction due to the volatilization of the internal additives.

[0028] Continue, see Figure 1a, which is a schematic diagram of an embodiment of a hybrid electrolyte system containing the solid electrolyte contact surface adjustment material of the present invention. As shown in the figure, the hybrid electrolyte system 1 includes a first particle 11, which is a first inorganic solid electrolyte; a second particle 12, which is selected from a second inorganic solid electrolyte, a passive ceramic material or an active material; and a bridge portion 13, which is located between the first particle 11 and the second particle 12, and the bridge portion 13 is formed by the solid electrolyte contact surface adjustment material, and the first particle 11 and the second particle 12 are connected to form a surface-to-surface ion transfer path. As mentioned above, the present invention uses additive materials, such as ionic liquids, to improve the fluidity of the polymer matrix, so that the polymer matrix has higher room temperature ion conductivity and poor mechanical properties, and can be filled between the first particle 11 and the second particle 12, so that the inorganic solid electrolyte (first particle) can achieve surface-to-surface or nearly wettable contact with another particle (solid electrolyte or active material surface) through the contact surface adjustment material, rather than the traditional solid electrolyte particles only through the contact point with another particle point-to-point ion transfer mode, so the present invention can reduce the interface resistance of the solid electrolyte. The inorganic solid electrolyte mentioned above may be, for example, an oxide solid electrolyte or a sulfide solid electrolyte or other inorganic solid electrolytes.

[0029] The surface-to-surface or wetting contact defined in the present invention can be as follows: Figure 1b As shown, if it is assumed that the first particle 11 is spherical with a radius of D1, and the second particle is also spherical with a radius of D2, the contact surface between the bridge portion 13 and the first particle 11 is arc length r1, and the central angle corresponding to the arc length r1 is θ1, and the arc length r1 is 2πD1*θ1 / 360; 0<θ1<90. The contact surface between the bridge portion 13 and the second particle 12 is arc length r2, and the central angle corresponding to the arc length r2 is θ2, and the arc length r2 is 2πD2*θ2 / 360, 0<θ2<90. Therefore, the first particle 11 and the second particle 12 conduct ion transmission through the contact surface arc lengths r1 and r2. In contrast, the point-to-point contact between the traditional solid electrolyte particle and another particle is only a single point on the radius, which can also be said to be r≒0 (θ≒0).

[0030] In addition to being used as an ion conductor in the mixed electrolyte system, the polymer matrix also serves as an adhesive and a film-forming agent to adhere the first particles 11 and the second particles 12 .

[0031] See also Figure 1c, which is a schematic diagram of another embodiment of the present invention. As shown in the figure, the surface of the bridge portion 13 that is not in contact with the first particle 11 and the second particle 12 is doped / arranged with a plurality of first dopants 14. The first dopant 14 can be a third inorganic solid electrolyte with a particle size smaller than the first particle 11 and the second particle 12, or a passive ceramic material (non-electrolyte oxide) that promotes film formation. Furthermore, the first dopant 14 is also extended to the outer surface of the first particle 11 and / or the second particle 12, such as Figure 1d In addition, when the second particle 12 is an active material, the first dopant 14 can be a conductive material. The conductive material can be selected from graphite, acetylene black, carbon black, carbon tube, carbon fiber, graphene or a mixture of any two or more of the above materials.

[0032] See also Figure 1e , which is a schematic diagram of another embodiment of the present invention. As shown in the figure, the bridging portion 13 is also mixed with a second dopant 15, which can be a nano-scale passive ceramic material or an inorganic solid electrolyte particle. The relevant instructions and effects of mixing the second dopant 15 into the solid electrolyte contact surface adjustment material have been described previously and will not be repeated here. In addition, when the second particle 12 is an active material, the second dopant 15 can be a conductive substance, or a mixture of nano-scale particles (oxides or / solid electrolytes) and a conductive substance. This conductive substance can be selected from graphite, acetylene black, carbon black, carbon tubes, carbon fibers, graphene, or a mixture of any two or more of the above materials.

[0033] The embodiment in which the second dopant 15 is mixed in the bridge portion 13 can be combined with the above Figure 1c or Figure 1d In combination with the embodiments, for example Figure 1f As shown, in addition to the second dopant 15 mixed in the bridge portion 13 , a plurality of first dopants 14 are also doped / disposed on the surface of the bridge portion 13 that is not in contact with the first particle 11 and the second particle 12 .

[0034] In the following embodiments, components having the same structure, material or characteristic conditions will be described with the same names and component symbols as before.

[0035] See also Figure 2a, which is a schematic diagram of another embodiment of a hybrid electrolyte system containing the solid electrolyte contact surface adjustment material of the present invention. As shown in the figure, this hybrid electrolyte system 2 includes a first particle 11, which is a first inorganic solid electrolyte; a second particle 12, which is selected from a second inorganic solid electrolyte, a passive ceramic material or an active material; and a first shell 21, which covers the outer surface of the first particle 11; wherein the first shell 21 is formed by the above-mentioned solid electrolyte contact surface adjustment material, and the solid electrolyte contact surface adjustment material connects the first particle and the second particle to form a non-single-point ion transfer pathway. Since the solid electrolyte contact surface adjustment material is a material with poor mechanical strength properties, the contact between the second particle 12 and the first shell 21 composed of the solid electrolyte contact surface adjustment material will present a surface contact method that is approximately infiltration-type, rather than point-to-point, such as Figure 2a Local zoom in Figure 2a' As shown. In the subsequent components constructed using solid electrolyte contact surface adjustment materials, when they touch hard or fixed-shaped materials (particles), they will all be in such a wetted surface contact.

[0036] See also Figure 2b , compared to Figure 2a The difference of the embodiment is that the outer surface of the first shell layer 21 is further doped / arranged with a plurality of first dopants 14. Figure 2c , compared to Figure 2b The difference of the embodiment is that the first shell layer 21 is mixed with the second dopant 15. Figure 2d A second shell layer 22 may also be formed on the outer surface of the second particle 12. The second shell layer 22 is also formed by the above-mentioned solid electrolyte contact surface adjusting material.

[0037] See also Figure 2e , compared to Figure 2d The difference of the embodiment is that the outer surface of the first shell layer 21 and / or the second shell layer 22 is further doped / disposed with a plurality of first dopants 14. Figure 2f , compared to Figure 2e The difference of the embodiment is that the first shell layer 21 and / or the second shell layer 22 is mixed with the second dopant 15.

[0038] See also Figure 3a, which is another embodiment schematic diagram of a hybrid electrolyte system containing the solid electrolyte contact surface adjustment material of the present invention. As shown in the figure, this hybrid electrolyte system 3 includes a first particle 11, which is a first inorganic solid electrolyte; a second particle 12, which is a second inorganic solid electrolyte or active material; a first shell 21, which covers the outer surface of the first particle 11; a second shell 22, which covers the outer surface of the second particle 12; and a bridge 13, which is located between the first shell 21 and the second shell 22, and connects or connects the first shell 21 and the second shell 22; wherein the first shell 21, the second shell 22 and the bridge 13 are all formed by the solid electrolyte contact surface adjustment material, and the solid electrolyte contact surface adjustment material becomes the surface-to-surface ion transfer path of the first particle and the second particle.

[0039] See also Figure 3b , compared to Figure 3a The difference of the embodiment is that the surface of the bridge portion 13 that is not in contact with the first shell layer 21 and the second shell layer 22 is doped / disposed with a plurality of first dopants 14. Figure 3c , compared to Figure 3b The difference of the embodiment is that the first dopant 14 is further extended to the outer surface of the first shell layer 21 and / or the second shell layer 22.

[0040] See also Figure 3d , compared to Figure 3c The difference of the embodiment is that the solid electrolyte contact surface adjustment material constituting the first shell layer 21 , the second shell layer 22 and the bridge portion 13 is mixed with a second dopant 15 .

[0041] See also Figure 3e , compared to Figure 3d The difference of the embodiment is that the first dopant 14 is further extended to the outer surface of the first shell layer 21 and / or the second shell layer 22.

[0042] In the above embodiments, when the second particle 12 is an active material, the hybrid electrolyte system can be applied to the electrode layer, and an artificial passivation film can be formed on the surface of the second particle 12 to prevent the electrolyte (solid electrolyte contact surface adjustment material) from causing structural degradation of the active material, and the resulting reduction in surface conductivity and the rate at which lithium ions pass through the surface layer. For example, Figure 1g , an artificial passivation film 16 may also be formed on the surface of the second particle 12. Figure 2g , Figure 2h and Figure 3fAs shown, an artificial passivation film 16 may also be formed on the surface of the second particle 12. The artificial passivation film 16 is sandwiched between the second particle 12 and the second shell 22. The main purpose of the artificial passivation film 16 is to reduce or avoid excessive contact between the solid electrolyte contact surface adjustment material component and the second particle 12. The artificial passivation film 16 can be divided into a non-solid electrolyte series and a solid electrolyte series based on whether the ion conductivity is good or not. The thickness of the artificial passivation film 16 is roughly less than 100 nanometers. The non-solid electrolyte series can be a conductive material, a ceramic material without lithium ions, or a mixture of these two materials. The ceramic material without lithium can be selected from zirconium oxide, silicon oxide, aluminum oxide, titanium oxide or gallium oxide.

[0043] When the second particle 11 is selected from an inorganic solid electrolyte or a passive ceramic material, the hybrid electrolyte system can be applied to the isolation layer, and the hybrid electrolyte system needs to have an ion supply material, such as a salt. Furthermore, when the first particle 11 and the second particle 12 are both inorganic solid electrolytes and do not have a shell structure, the first particle 11 and the second particle 12 must select the type of material depending on the location of the battery component to be applied. For example, when the hybrid electrolyte system is applied to the positive electrode side, the first particle 11 and the second particle 12 can select lithium aluminum titanium phosphate (LATP) or lithium blue zirconium oxide (LLZO), and when the hybrid electrolyte system is applied to the negative electrode side, the first particle 11 and the second particle 12 can select LLZO to avoid the LATP containing titanium element from generating a reduction reaction when used in the negative electrode. However, when the outer surface of the first particle 11 and the second particle 12 has a shell, there is no need to adjust the type of solid electrolyte used according to the type of the electrode layer (positive electrode or negative electrode), that is, the first particle 11 and the second particle 12 can both be low-cost LATP and applied to the positive and negative electrodes.

[0044] In summary, the first dopant 14 of the present invention can be selected from three types. The first type is a solid electrolyte, and the particle size is smaller than the first particle 11 and the second particle 12; the second type is a passive ceramic material, which can be used as a film-forming reinforcement material in addition to reducing the amount of solid electrolyte contact surface adjustment material used; the third type is a conductive material, which is mainly used in the polar layer. The first and second types are applicable to both the polar layer and the interlayer.

[0045] The particle size or size of the second dopant 15 described in the present invention is nanometer-level, and can also be selected from three types. The first type is a solid electrolyte; the second type is a passive ceramic material, which can be used as a film-forming reinforcement material in addition to reducing the amount of solid electrolyte contact surface adjustment material used; the third type is a conductive material, which is mainly used in the polar layer. The first and second types are applicable to both the polar layer and the interlayer.

[0046] For example, when the second particle 12 is an active material, the second dopant (nanoscale particle) 15 mixed or filled with the solid electrolyte adjustment material (as a bridge and / or shell) can be a solid electrolyte, a passive ceramic material, or a conductive substance, or a mixture of any two or more of the above materials. Similarly, if the second particle 12 is an active material, the surface of the first particle 11, the second particle 12, or any surface of the first shell 21, the second shell 22, and the bridge 13 can be provided with a first dopant 14, and the first dopant 14 can be a solid electrolyte, a passive ceramic material, or a conductive substance, or a mixture of any two or more of the above materials.

[0047] See also Figure 4 , which is a graph of the ion conduction characteristics of the solid electrolyte contact surface adjustment material of the present invention and the oxide solid electrolyte LATP at low and high frequencies. In this figure, curve A represents LATP, curve B represents the solid electrolyte contact surface adjustment material of the present invention without ion supply material, and curve C represents a mixed electrolyte system containing the solid electrolyte contact surface adjustment material of the present invention (which can be regarded as a mixture of 70% A and 30% B by weight), which does not contain ion supply material, and LATP is equivalent to the first particle in the specification. Curve D is the component of curve C with lithium ions added. It can be seen from the figure that in the high frequency region, the oxide solid electrolyte LATP has better ion conductivity. Therefore, it can be seen that in the high frequency state, the movement mode of ions tends to be mainly in the solid oxide homogeneous structure. This homogeneous structure generally refers to the homogeneous structure of the crystal or glass or solid solution. On the contrary, in the medium and low frequency region, the solid electrolyte contact surface adjustment material of the present invention without ion supply material performs better. Therefore, it can be seen that in the medium and low frequency region, the movement mode of ions is mainly solid / solid interface (heterogeneous phase). The solid electrolyte contact surface adjustment material of the present invention has better performance because it produces a better surface contact mode (similar to liquid wetting contact). Therefore, the hybrid electrolyte of the present invention is a mixture of the components of curve A and curve B in a specific ratio. It can be seen from the figure that after such a mixture, the ion conduction characteristics (curve C or D) can achieve the best low-frequency and high-frequency uniformity.

[0048] In addition, by Figure 4From the curve C, it can be found that when a hybrid solid electrolyte system is obtained by mixing a contact surface adjustment material with a volume percentage of A0 and a solid electrolyte with a volume percentage of B0 (A0 + B0 ≒ 100, A0 is 30 - 40, and B0 is 70 - 60) (when the second dopant 15 is a solid electrolyte, it is also included in the percentage B), if the contact surface adjustment material is used to contact the active material in the electrode layer, the ratio of the solid electrolyte adjustment material to the solid electrolyte in this hybrid electrolyte system can be appropriately adjusted to A1 for the contact surface adjustment material and B1 for the solid electrolyte, where A1 + B1 = 100 and 50 < A1 < 100. Conversely, if this hybrid electrolyte system is far from the active material, the volume of the solid electrolyte adjustment material in the entire hybrid electrolyte system is A2, and the solid electrolyte is B2, where A2 + B2 = 100 and 50 < B2 < 100. In this way, it will be possible to more effectively meet the low-frequency conduction requirements closer to the active material, and the high-frequency conduction requirements are located farther from the active material, so a higher solid electrolyte content is used. That is to say, as the distance from the outer surface of the active material increases from near to far, the contact surface adjustment material shows a volume ratio content distribution that decreases from high to low in the hybrid solid electrolyte system. In other words, for a battery composed of this hybrid electrolyte system, the battery includes an active material layer and a separator layer. When this hybrid electrolyte system is applied to the separator layer, the volume content of the solid electrolyte contact surface adjustment material is less than the volume content of the solid electrolyte in this hybrid electrolyte system. When this hybrid electrolyte system is applied to the active material layer, the closer to the surface of the active material, the higher the volume content of the solid electrolyte contact surface adjustment material compared to the volume content of the solid electrolyte in this hybrid electrolyte system.

[0049] In summary, the present invention proposes a novel solid electrolyte contact surface adjustment material and its hybrid electrolyte system applied to an electrochemical system (such as a lithium-ion secondary battery). This solid electrolyte adjustment material is mainly composed of a polymer substrate that allows metal ions to move inside the material and an additive material that can dissociate metal salts and act as a plasticizer, so as to form a wetting contact that is more similar to a liquid or a face-to-face contact pattern on the contact surface between the oxide solid electrolyte particles and another particle material, thereby effectively reducing the high interfacial impedance problem of the oxide solid electrolyte.

[0050] However, the above are only the preferred embodiments of the present invention and are not used to limit the scope of implementation of the present invention. Therefore, all equivalent changes or modifications made according to the features and spirit described in the scope of the present invention application should be included in the claims of the present invention.

[0051]

Description of the Drawings

[0052] 1, 2, 3 Hybrid electrolyte system

[0053] 11 First Particle

[0054] 12 Second Particle

[0055] 13 Bridge

[0056] 14 First dopant

[0057] 15 Second dopant

[0058] 16 Artificial passive membrane

[0059] 21 First Shell

[0060] 22 Second Shell

Claims

1. A solid electrolyte contact surface adjustment material, which is used in an electrochemical system and is located on the surface of a solid electrolyte, wherein the solid electrolyte contact surface adjustment material is mainly composed of a polymer matrix that allows metal ions to move inside the material and an additive that can dissociate metal salts and serve as a plasticizer, wherein the polymer matrix is ​​selected from polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol methyl ether, polyethylene glycol dimethyl ether, polyethylene oxide / 2, (2-methoxyethoxy) -ethyl glycidyl ether copolymer, The solid electrolyte contact surface adjustment material further comprises a crystallization inhibiting material, and the crystallization inhibiting material is selected from polyethyl methacrylate, polymethyl methacrylate, polyethylene oxide, polycyanoacrylate, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl chloride-polyethyl methacrylate, polyoxyethylene-polymethyl methacrylate, polyacrylonitrile methyl methacrylate copolymer, polyvinyl alcohol-polyvinylidene fluoride, polyacrylonitrile-polyvinyl alcohol; polycarbonate; cyclic carbonate; polysiloxane; polyester; polyvinylidene fluoride co-hexafluoropropylene, polyvinylidene fluoride, polycaprolactone.

2. The solid electrolyte contact surface adjustment material as claimed in claim 1 further comprises an ion supply material.

3. The solid electrolyte contact surface adjustment material as claimed in claim 1, wherein the additive material is a plastic crystalline electrolyte (PCEs) or an ionic liquid.

4. The solid electrolyte contact surface adjusting material according to claim 1, wherein: The polycarbonate is selected from poly(ethylene oxide) vinyl carbonate, poly(ethylene carbonate), poly(propylene carbonate), poly(ethyl glycidyl ether carbonate), and poly(tert-butyl glycidyl ether carbonate); The cyclic carbonate is polytrimethyl carbonate; The polysiloxane is selected from polydimethylsilane, polydimethylsilane ethylene oxide copolymer, polyethyleneoxysiloxane, and polyhedral siloxane oligomer; The polyester is selected from ethylene adipate, ethylene succinate, and ethylene malonate.

5. The solid electrolyte contact surface adjustment material as described in claim 1, wherein the solid electrolyte contact surface adjustment material is also mixed with a second dopant, whose size is nanometer level, and the second dopant is selected from an inorganic solid electrolyte, a passive ceramic material, a conductive material or a mixture of two or more of the above materials.

6. A hybrid electrolyte system comprising: a first particle, which is a first inorganic solid electrolyte; second particles selected from a second inorganic solid electrolyte, a passive ceramic material, or an active material; and a bridge portion, which is located between the first particle and the second particle, the bridge portion is formed by a solid electrolyte contact surface adjustment material, and the first particle and the second particle are connected to form a surface-to-surface ion transfer pathway, wherein the solid electrolyte contact surface adjustment material is a mixture of a polymer matrix that allows lithium ions to move inside the material and an additive material that can dissociate lithium salts and serve as a plasticizer, wherein the polymer matrix is ​​selected from polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol methyl ether, polyethylene glycol dimethyl ether, polyethylene oxide / 2, (2-methoxyethoxy) -ethyl glycidyl ether copolymer, The central angle corresponding to the arc length of the contact surface between the bridge portion and the first particle is θ1, and 0<θ1<90, the central angle corresponding to the arc length of the contact surface between the bridge portion and the second particle is θ2, and 0<θ2<90, The solid electrolyte contact surface adjustment material further comprises a crystallization inhibiting material, and the crystallization inhibiting material is selected from polyethyl methacrylate, polymethyl methacrylate, polyethylene oxide, polycyanoacrylate, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl chloride-polyethyl methacrylate, polyoxyethylene-polymethyl methacrylate, polyacrylonitrile methyl methacrylate copolymer, polyvinyl alcohol-polyvinylidene fluoride, polyacrylonitrile-polyvinyl alcohol; polycarbonate; cyclic carbonate; polysiloxane; polyester; polyvinylidene fluoride co-hexafluoropropylene, polyvinylidene fluoride, polycaprolactone.

7. A hybrid electrolyte system comprising: a first particle, which is a first inorganic solid electrolyte; second particles selected from a second inorganic solid electrolyte, a passive ceramic material, or an active material; and A first shell layer covering the outer surface of the first particle; The first shell layer is formed by a solid electrolyte contact surface adjustment material, and the first particle and the second particle are connected to form an ion transfer path, wherein the solid electrolyte contact surface adjustment material is a mixture of a polymer matrix that allows metal ions to move inside the material and an additive material that can dissociate metal salts and serve as a plasticizer, wherein the polymer matrix is ​​selected from polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol methyl ether, polyethylene glycol dimethyl ether, polyethylene oxide / 2, (2-methoxyethoxy) -ethyl glycidyl ether copolymer, The solid electrolyte contact surface adjustment material further comprises a crystallization inhibiting material, and the crystallization inhibiting material is selected from polyethyl methacrylate, polymethyl methacrylate, polyethylene oxide, polycyanoacrylate, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl chloride-polyethyl methacrylate, polyoxyethylene-polymethyl methacrylate, polyacrylonitrile methyl methacrylate copolymer, polyvinyl alcohol-polyvinylidene fluoride, polyacrylonitrile-polyvinyl alcohol; polycarbonate; cyclic carbonate; polysiloxane; polyester; polyvinylidene fluoride co-hexafluoropropylene, polyvinylidene fluoride, polycaprolactone. 8 . The hybrid electrolyte system as claimed in claim 7 , wherein a second shell layer is formed on the outer surface of the second particle, and the second shell layer is formed by the solid electrolyte contact surface adjusting material.

9. A hybrid electrolyte system as described in claim 8, wherein the outer surface of the second shell is also doped / arranged with a plurality of first dopants, and when the second particle is selected from a second inorganic solid electrolyte or a passivation ceramic material, the first dopant is selected from an inorganic solid electrolyte, a passivation ceramic material or a mixture thereof; when the second particle is an active material, the first dopant is selected from an inorganic solid electrolyte, a passivation ceramic material, a conductive material or a mixture of any two or more thereof. 10 . The hybrid electrolyte system as claimed in claim 8 , wherein when the second particle is an active material, a surface of the second particle has an artificial passivation film, and the artificial passivation film is located between the second particle and the second shell layer.

11. The hybrid electrolyte system as described in claim 8 further includes a bridging portion, which is located between the first shell layer and the second shell layer, and connects the first shell layer and the second shell layer, and the bridging portion is formed by the solid electrolyte contact surface adjustment material, wherein the central angle corresponding to the arc length of the contact surface between the bridging portion and the first particle is θ1, and 0<θ1<90, and the central angle corresponding to the arc length of the contact surface between the bridging portion and the second particle is θ2, and 0<θ2<90.

12. A hybrid electrolyte system as described in claim 6 or 11, wherein the surface of the bridging portion that is not in contact with the first particle and the second particle is also doped / arranged with a plurality of first dopants, and when the second particle is selected from a second inorganic solid electrolyte or a passivation ceramic material, the first dopant is selected from an inorganic solid electrolyte, a passivation ceramic material or a mixture thereof; when the second particle is an active material, the first dopant is selected from an inorganic solid electrolyte, a passivation ceramic material, a conductive material or a mixture of any two or more thereof. 13 . The hybrid electrolyte system as claimed in claim 12 , wherein the first dopant is further extended to the outer surface of the first particle and / or the second particle.

14. A hybrid electrolyte system as described in claim 6, 7 or 11, wherein the solid electrolyte contact surface adjustment material is also mixed with a second dopant, whose size is nanometer level, and when the second particle is selected from a second inorganic solid electrolyte or a passivation ceramic material, the second dopant is selected from an inorganic solid electrolyte, a passivation ceramic material or a mixture thereof; when the second particle is an active material, the second dopant is selected from an inorganic solid electrolyte, a passivation ceramic material, a conductive material or a mixture of any two or more thereof.

15. The hybrid electrolyte system as claimed in claim 6 or 7, wherein when the second particle is an active material, the surface of the second particle further has an artificial passivation film.

16. A hybrid electrolyte system as described in claim 7, wherein the outer surface of the first shell is also doped / arranged with a plurality of first dopants, and when the second particle is selected from a second inorganic solid electrolyte or a passivation ceramic material, the first dopant is selected from an inorganic solid electrolyte, a passivation ceramic material or a mixture thereof; when the second particle is an active material, the first dopant is selected from an inorganic solid electrolyte, a passivation ceramic material, a conductive material or a mixture of any two or more thereof.

17. The hybrid electrolyte system according to claim 6 or 7, further comprising a crystallization inhibiting material and / or an ion supplying material.

18. The hybrid electrolyte system as claimed in claim 6 or 7, wherein the additive material is a plastic crystalline electrolyte (PCEs) or an ionic liquid.

19. The hybrid electrolyte system according to claim 6 or 7, wherein: The polycarbonate is selected from poly(ethylene oxide) vinyl carbonate, poly(ethylene carbonate), poly(propylene carbonate), poly(ethyl glycidyl ether carbonate), and poly(tert-butyl glycidyl ether carbonate); The cyclic carbonate is polytrimethyl carbonate; The polysiloxane is selected from polydimethylsilane, polydimethylsilane ethylene oxide copolymer, polyethyleneoxysiloxane, and polyhedral siloxane oligomer; The polyester is selected from ethylene adipate, ethylene succinate, and ethylene malonate.

Citation Information

Patent Citations

  • Solid-state electrolyte applied to lithium battery and preparation method of solid-state electrolyte

    CN108199081A

  • Polar layer composite material

    CN110165221A

  • Polymer-coated solid electrolyte and all-solid secondary battery using the same

    JP2010033876A

  • Composite solid electrolyte for secondary battery and method for producing same

    JP2019530195A